Algorithms for solving generalized equilibrium problems and fixed points of nonexpansive semigroups in Hilbert spaces - Suthep Suantai (2018)
In this article, strong convergence theorems by the modified viscosity approximation method associated with Meir-Keeler contractions are proved for solving fixed point problems of a nonexpansive semigroup and generalized equilibrium problems in a Hilbert space. © 2014 Copyright Taylor & Francis Group, LLC.